2017
DOI: 10.1109/tcad.2016.2620902
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of Mask Fracturing Heuristics

Abstract: Aggressive resolution enhancement techniques such as inverse lithography (ILT) often lead to complex, non-rectilinear mask shapes which make mask writing extremely slow and expensive. To reduce shot count of complex mask shapes, mask writers allow overlapping shots, due to which the problem of fracturing mask shapes with minimum shot count is NP-hard. The need to correct for e-beam proximity effect makes mask fracturing even more challenging. Although a number of fracturing heuristics have been proposed, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…All heuristics are run on a single thread and we report the wall time for all the methods. We demonstrate results for CD tolerance γ = 2nm, σ = 6.25nm and ∆ p = 1nm as done in the previous work on benchmarking [16]. We shall report results for ten real ILT mask shapes and ten generated benchmark shapes with known optimal solution, all of which are available at the benchmarking website [17] 4 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All heuristics are run on a single thread and we report the wall time for all the methods. We demonstrate results for CD tolerance γ = 2nm, σ = 6.25nm and ∆ p = 1nm as done in the previous work on benchmarking [16]. We shall report results for ten real ILT mask shapes and ten generated benchmark shapes with known optimal solution, all of which are available at the benchmarking website [17] 4 .…”
Section: Resultsmentioning
confidence: 99%
“…However, since a mask contains billions of polygons, a practical fracturing method must be extremely fast for any given polygon. In this work, we focus on solving the fixed dose model-based fracturing problem with rectangular shots, as done in the benchmarking work [16]. Although variable-dose shots [18] and non-rectangular shots [19,20] have been proposed, Elayat et al have concluded that fixed-dose fracturing with rectangular shots is the most viable approach to reduce shot count without significant changes to the mask writing tools [21].…”
Section: Problem Descriptionmentioning
confidence: 99%
See 3 more Smart Citations